2019
DOI: 10.1007/s11750-019-00505-5
|View full text |Cite
|
Sign up to set email alerts
|

Reducing pollutant emissions in a waste collection vehicle routing problem using a variable neighborhood tabu search algorithm: a case study

Abstract: This paper focuses on designing waste collection routes with a single landfill using eco-efficiency as a performance indicator. In this problem, there are a limited number of heterogeneous vehicles based at a single depot. Empty vehicles leave the depot, collect waste from a set of locations and drop off the collected waste at a specific landfill. Then, vehicles leave the landfill and may collect more waste from other locations or return empty to the depot. Traditional performance indicators in vehicle routing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 70 publications
(80 reference statements)
0
18
0
Order By: Relevance
“…Other recent studies have also utilized these algorithms and highlighted their higher performance. [35][36][37][38] These beneficial studies have indicated that greedy, interroute, intraroute, and Tabu are interlinked and high-performance algorithms for solving vehicle routing issues. Accordingly, the current study adopts and subsequently explains these algorithms.…”
Section: Uav Routing Problems and Key Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent studies have also utilized these algorithms and highlighted their higher performance. [35][36][37][38] These beneficial studies have indicated that greedy, interroute, intraroute, and Tabu are interlinked and high-performance algorithms for solving vehicle routing issues. Accordingly, the current study adopts and subsequently explains these algorithms.…”
Section: Uav Routing Problems and Key Algorithmsmentioning
confidence: 99%
“…Lastly, a Tabu search is purposed to make improvements to the promising solutions obtained from the upper layers. Other recent studies have also utilized these algorithms and highlighted their higher performance 35–38 . These beneficial studies have indicated that greedy, interroute, intraroute, and Tabu are interlinked and high‐performance algorithms for solving vehicle routing issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some works are devoted to carbon emission reduction and other environmental protection aspects [13,14]. In the field of waste collection, Molina et al [15] use eco-efficiency as a performance indicator which takes carbon dioxide emissions and pollutant emissions into account for the waste collection route decision. Farrokhi-Asl et al [16] present a multiobjective mathematical model considering a sustainable collection network for the collection, treatment, recycling, and disposal of hazardous waste.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, for metaheuristic method, previous research used split-based adaptive tabu search (SATS) [64], time varying (TVa) and particle swarm optimization with greedy mutation operator (PSOGMO) [89], non-dominated sorting genetic algorithm II (NSGA II) [32,93], Ant colony optimization (ACO) [90], variable neighborhood search [94], variable neighborhood tabu search algorithm [91], and GA [92]. Besides, in multiobjective GVRP there are some hybrid methods that have been implemented such as exact-exact, exactmetaheuristic, and heuristic-metaheuristic.…”
Section: Gvrp With Multi-objectivementioning
confidence: 99%